A Portfolio for Millennial Learners in Essay Writing Class - Puspita, Nurul (Universitas Islam Negeri Raden Intan Lampung, 2019)
Millennial learners like to do a trial and error. Their critical thinking always changes all the times. In addition, they attempt to use their best effort in finding some solutions of their problems. In doing such writing, a millennial portrays their point of view in arranging a logical order of writing. It commonly names essay writing. Essay writing begins with clustering any ideas related to particular topic or issue. Then, they can start to design an outline. By using the outline, millennial continues the activity into drafting and revising. The stages are enough complicated. Furthermore, the practitioner especially a lecture should give more critics or comment to the writing. A portfolio can be used to check their progress of self-correction of peer correction. This media is used to collect their works into a bundle. There will be some writing which has been produced then they can easily correct the mistakes of the writing. In this article, the lecturer uses portfolio in essay writing class with the subject a millennial learner. They should produce some themes or topics that have been designed. Therefore, this media really help them in correcting their writing. Thus, they might get a good result of essay writing.